Influence of carbon source, agitation and aeration rates for production yeast biomass which potential of use for biological control (Research, Society and Development, 2020)
The fermentation processes are used to promote better results when it is desired to increase the biomass of organisms that can be used in biological control. Thus, the aim of this work was to expand the scale of production of biomass of yeasts that have potential for biological control. A total of five strains of yeasts isolated from natural microflora of tropical fruits, a strain was selected and evaluated for the influence of the carbon source, cultivation orbital shaker and bioreactor. The tests performed demonstrate that the use of invert sugar as carbon source favored production of biomass material when compared to that obtained with glucose. The bioreactor cultivation of the yeast strain has enhanced performance, since it favors an increase of 24.12% (6.47 to 8.03 g.L-1) in biomass production when compared to the fermentation orbital shaker and that may be associated with increased agitation and aeration rate.